Pengaruh Kepemimpinan Transformasional, Iklim Inovasi, Efikasi Diri Terhadap Kreativitas Karyawan Pada Industri Pembuatan Gerabah Di Desa Kasongan, Kabupaten Bantul - Muhammad Yusuf Sholeh Sudjijana (JURNAL EKOBIS DEWANTARA, 2019)
ABSTRACT The purpose of this study was to determine the Effect of Transformational Leadership, Innovation Climate, Self Efficacy on Employee Creativity in the Industry of Pottery Making in Kasongan Village, Bantul Regency on CV. Sokowatu Jaya, CV. Mata Hati, Jambul Ceramic in Kasongan, Bantul Regency, Yogyakarta. This research is a quantitative research. The population in this study are several employees "CV. Sokowatu Jaya, CV. Mata Hati, and Jambul Ceramic ". Data collection was performed using a questionnaire method. The data analysis technique used is a regression technique that is supported by the t test and classical assumptions, the data that has been obtained is processed using SPSS 21. The results of this study indicate that transformational leadership has a significant positive effect on self-efficacy; transformational leadership has a significant positive effect on innovation climate; self-efficacy has a significant positive effect on employee creativity; innovation climate has a significant positive effect on employee creativity;